A cultura dos terreiros. Um estudo de caso no candomblé na Bahia - Agier, Michel (Revista de Antropologia, 1996)
By considering "candomblé" as the culture of a place , this article tries to surpass the simple opposition between the notion or "candomblé" as an ethnic religion, and lhe notion of "candomblé" as a service offered in an indistinct religious market. In the introduction, this attempt is situated within the theoretical framework of Afro-Brazilian studies, which is briefly reviewed. ln the case study, which is then presented (the "terreiro" in Vila Flaviana, Salvador, Bahia) , we try to give an account of tensions lying at the root of the cultural dynainics of the "terreiros". Studies based on the history or conversions and the social networks involved make it possible to evidence the internal conflicts which affect the interpretation of "candomblé"